The structural adjustment credit project = (The World Bank in Vietnam (WB), 2003)
The main objectives of the Power Sector Rehabilitation and Expansion Project are to: 1) assist the Government in optimizing its investment decisions and help meet demand growth; 2) help improve the efficiency of the power supply system be rehabilitation and reinforcing transmission and distribution systems